How Indoor Air Quality Affect Employees Health and Performance in Different Level Companies. - ALMEZEININ, KHALOUD (2023)
Employee performance and health are significantly impacted by the work environment. Indoor air quality (IAQ) has a significant impact on employees' health and productivity in the office setting. Due to the lack of studies done to evaluate IAQ influence inside low and high-cost companies in UAE, this study was motivated to fill this gap and to evaluate the effects of IAQ within two different levels of working environments. Poor Indoor Air Quality is a relevant area of concern which has a direct impact on an employee's performance (Azuma et al., 2017). The purpose of this study was to examine the relationship between IAQ exposure and associated risks on employee health and performance in two different companies’ levels. Two different levels of companies were chosen as a case study where the best methodology applied. Data were collected using quantitative method (Field measurement) where we utilized three devices in order to reach the problem causes and to know more about our research question like (4 in 1 Environmental Meter, Air quality CO2 meter, and a sound level alert), a survey questionnaire utilized to know employee’s satisfaction and reaction with surrounding working environment, and finally a employees interview were conduct to elaborate more on their perspective regarding indoor air quality. The survey questionnaire which was distributed to all employees who were working in those companies revealed multiple evidence and facts. The questioning where mainly focusing on employee’s perspective to multiple aspects like: the amount of time that employees spend in their workplace, glare presence, windows availability, presence of printers/photocopiers, and scanners, wet ceilings, ventilation system, type of furniture, thermal comfort, as well as flooring materials. Respondents from low cost company showed that there was evidence of inadequate indoor quality from different aspects, while high-cost company showed that there was sufficient indoor quality from many manners perspective. Field measurements shed light on specific areas like: the levels of carbon dioxide (CO2) in the workplace, humidity levels, air velocity, temperature, and noise source. These measurements discovered the presence of multi factors in low cost companies associated in causing poor indoor quality. Moving forward the results revealed that there are many different problems derived from working environments. This paper correspondingly presents some new ideas and scopes that will help engineering companies to recognize the impact of poor IAQ on their employees and analyze the reasons that lead to weak IAQ in their companies as well as to know this issue could be addressed in order to maintain positive atmosphere that enhance employee’s performance and health.